p38 MAP kinase mediates apoptosis through phosphorylation of BimEL at Ser-65. - Cai, B; Chang, S; Becker, E; Bonni, A; Xia, Z (2006)
The stress-activated c-Jun N-terminal protein kinase (JNK) and p38 mitogen-activated protein (MAP) kinase (p38) regulate apoptosis induced by several forms of cellular insults. Potential targets for these kinases include members of the Bcl-2 family proteins, which mediate apoptosis generated through the mitochondria-initiated, intrinsic cell death pathway. Indeed, the activities of several Bcl-2 family proteins, both pro- and anti-apoptotic, are controlled by JNK phosphorylation. For example, the pro-apoptotic activity of Bim(EL), a member of the Bcl-2 family, is stimulated by JNK phosphorylation at Ser-65. In contrast, there is no reported evidence that p38-induced apoptosis is due to direct phosphorylation of Bcl-2 family proteins. Here we report evidence that sodium arsenite-induced apoptosis in PC12 cells may be due to direct phosphorylation of Bim(EL) at Ser-65 by p38. This conclusion is supported by data showing that ectopic expression of a wild type, but not a non-phosphorylatable S65A mutant of Bim(EL), potentiates sodium arsenite-induced apoptosis and by experiments showing direct phosphorylation of Bim(EL) at Ser-65 by p38 in vitro. Furthermore, sodium arsenite induced Bim(EL) phosphorylation at Ser-65, which was blocked by p38 inhibition. This study provides the first example whereby p38 induces apoptosis by phosphorylating a member of the Bcl-2 family and illustrates that phosphorylation of Bim(EL) on Ser-65 may be a common regulatory point for cell death induced by both JNK and p38 pathways.